Effect of hypoxia in the post-hatching development of the salmon (Salmo salar L.) spinal cord - Rojas, Mariana; Hernández, Hilda; Smok, Carolina; Pellón, Mario; Sandoval, Cristian; Salvatierra, Renato; Birditt, Katherine; Castro, Rodrigo (Frontiers in Marine Science, 2024)
Introduction Hypoxia has a teratogenic effect on the fish during embryonic development. Nevertheless, the effects on the larval stage are not yet known. Therefore, the aim of this study was to assess the effects of hypoxia on the number of neurons and their apoptotic rate in the spinal cord of Salmo salar alevins after hatching. Methods We used a total of 400 alevins, establishing both hypoxia and control (normoxia) groups (n = 8), considering post-hatching days 1, 3, 5, and 7, each with 50 individuals. Transversal sections of 50 μm thickness were cut from the alevin body. We performed cresyl-violet staining and counted the spinal cord neurons. Also, immunohistochemistry for HIF-1α and caspase-3 were used. For statistical analysis ANOVA one-way and Tukey's Test were used. Results HIF-1α was expressed in spinal neurons in both the hypoxic and normoxic groups, with the former being significantly higher. Both the hypoxic and normoxic groups evidenced the process of neuronal apoptosis, with the hypoxic groups demonstrating a higher significance. The number of neurons in the spinal cord was significantly lower in the hypoxic group. Discussion We found that when oxygen levels in the aquatic environment were low in Salmo salar farming alevins post-hatch, the number of spinal neurons dropped by half. These results contribute to increasing our knowledge of the biological development of salmon, in particular the genesis of the spinal cord, and the effects of hypoxic conditions on the development of this structure of the nervous system.